If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y = 3y + 18 Reorder the terms: 3y = 18 + 3y Add '-3y' to each side of the equation. 3y + -3y = 18 + 3y + -3y Combine like terms: 3y + -3y = 0 0 = 18 + 3y + -3y Combine like terms: 3y + -3y = 0 0 = 18 + 0 0 = 18 Solving 0 = 18 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -6(x-2)=12-3x | | 15+6x=25+5x | | 5x-2(-x-6)=-37 | | x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= | | 5(L+2)=36-5L | | 2y+15=19 | | -6.47-10.16= | | 4x^2+3=-18x | | +0-(+12)= | | ((5)/(2x+4)+4)=((-1)/(x+2)) | | 1=x+23 | | 6x+3=x-6 |